Evaluation of the Heavy Metal Bioremediation Potential of Indigenous Bacteria Isolated from Textile Effluents in Kano, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study aimed to assess the capability of indigenous bacteria isolated from textile effluents to bio-remove heavy metals at the Challawa industrial site in Kano, Nigeria. Physicochemical analyses of the textile effluent samples were conducted, and bacteria were isolated based on their physical, biochemical, and molecular traits. Bio-removal studies were conducted following standard procedures. The physicochemical parameters, including conductivity, total suspended particles, total dissolved solids, turbidity, dissolved oxygen, and biochemical oxygen demand, were found to have exceeded the WHO limits. Heavy metals were also found to be at initial concentrations significantly exceeding the WHO limits, namely: cadmium 0.12 ± 0.09 to 0.11 ± 0.6 mg/L, nickel 0.125 ± 0.04 to 0.103 ± 0.09 mg/L and lead 0.019 ± 0.10 to 0.018 ± 0.05 mg/L, except for zinc (0.468 ± 0.10 to 0.62 ± 0.08 mg/L), which was within limits. After a 21-day bio-removal period, the concentrations decreased significantly: cadmium (0.008 ± 0.02 to 0.006 mg/L), nickel (0.072 ± 0.15 to 0.045 ± 0.10 mg/L), lead (0.013 ± 0.02 to 0.010 ± 0.08 mg/L), and zinc (0.259 ± 0.15 to 0.072 ± 0.09 mg/L). These bacterial isolates achieved biomass reductions for cadmium (50.00%, 36.36%, 27.27%), nickel (56.31%, 50.50%, 42.40%), zinc (44.66%, 37.87%, 28.00%), and lead (47.37%, 33.33%, 31.58%), respectively. The study showed bio-removal after 21 days could be effective, signifying the possibility of applying bacteria in reducing environmental pollutants. This is a cost-effective and environmentally friendly approach to pollution reduction and enhancing ecosystem sustainability.
Keywords: Bioremediation; Heavy metals; Textile effluents; Bacterial isolates; Environmental pollution